Neoliberalism, massification and teaching transformative politics and international relations. Issue 3 (2nd July 2016) - Engel, Susan; Halvorson, Dan
ABSTRACT: 'Massification' describes the significant increase in the proportion of the global population seeking tertiary qualifications. It is a defining feature of the global international education sphere and is often seen as linked to negative outcomes such as declining academic standards and increasing managerialism in universities. Massification, however, is not wholly or even mostly a negative for the generations of new students who now have access to tertiary education. Education can still be a transformative experience for students exposed to a rich learning environment. The question this symposium raises is how the disciplines of politics and international relations can ensure they maintain quality teaching and learning for students from subject design to program design. The collection aims to initiate a disciplinary debate in Australia, which has hitherto been missing.